Pituitary pathological review in 201 dogs and cats - Polledo, Laura (2018)
In this study, we aimed to investigate the prevalence of pituitary changes and the range of its lesions in a general population of 201 dogs and cats. Clinical data, macroscopic and histopathologic data were carefully evaluated and further tests like special stains and immunohistochemical tests were applied and its significance is discussed in the context of the current literature, adding to the current knowledge of pituitary changes in dogs and cats, highlights debatable aspects of the current classification and helps pathologists and veterinarians with the diagnostic process. A wide range of abnormalities can occur within the pituitary gland which can lead to various endocrinological or neurological symptoms. With the exception of classic functional adenomas in dogs and horses, pituitary lesions are infrequently described in the veterinary literature. Given the increasing availability of advanced imaging in the diagnostic approach of both endocrine and neurological disease, a better understanding of the range of abnormalities encountered in the pituitary gland is desirable, especially with the progression in sampling or surgical treatment of the pituitary gland in dogs and cats. Approximately 10% of pituitary glands from asymptomatic humans contain abnormalities but the equivalent proportion in small animals is unknown. Pituitary glands from 136 dogs and 65 cats collected during routine necropsies were examined to determine the prevalence of pituitary lesions and their histopathological diagnosis. Sections were prepared with haematoxylin and eosin (HE), periodic acid-Schiff (PAS), Gordon and Sweet's reticulin and immunohistochemistry against several secreting hormonal peptides. Pituitary abnormalities were identified in 36/136 (26.4%) dogs and 10/65 (15.3%) cats. Pituitary cysts were the commonest lesion in dogs and cats, occurring in 18 (13.2%) dogs and 8 (12.3%) cats. Pituitary neoplasia was detected in 14.1% (12/85) of middle/old aged dogs; 1 (1.5%) cat had pituitary nodular hyperplasia. PAS proved useful for staining secretory granules in adrenocorticotropic hormone (ACTH)-positive adenomas and reticulin stain helped differentiate them from hyperplasia. These tumours were uniformly PAS positive with a loss of the normal reticulin network. One dog had a pituitary carcinoma with marked infiltration into the dorsal thalamus. Other pituitary abnormalities included: secondary metastatic neoplasia (2 dogs), hypophysitis (4 dogs, 1 cat). In the majority of cases the lesion was subclinical and could be considered incidental; of those dogs and cats with pituitary lesions, only 4 dogs (2.9%) and no cats demonstrated clinical manifestations of their pituitary disease ante mortem. Pituitary abnormalities are common in dogs and cats and their wider clinical relevance requires further investigation. Derived from this work and in collaboration with clinicians from Pride Veterinary Hospital, a unique case report of a dog presenting with inflammatory hypophysitis and hypothalamitis of suspected autoimmune origin with detailed clinical, magnetic resonance imaging (MRI), histology and immunohistochemistry findings which to our knowledge was reported. The case was initially misdiagnosed as a tumour by MRI; the correct diagnosis was made at post-mortem. We feel the value of this case report is in alerting clinicians that inflammatory conditions of the pituitary gland should be considered as potential differential diagnoses of suprasellar masses. Lymphocytic hypophysitis should be considered in the differential diagnoses of pituitary mass lesions, because it warrants very different management and treatment. In addition to the new information relevant to MRI interpretation, the report contains important clinical and pathological information on this previously unreported lesion. The study of the case has been thorough, including the integration of several specialities and has the potential to improve the diagnosis of future cases.